As the Pendulum Swings? The Politics of Crime Policy in San Francisco - Bisharat, George (Brazilian Journal of Empirical Legal Studies, 2023)
This article reviews recent oscillations in crime policy in the City and County of San Francisco, California, particularly as represented in the 2019 election of Chesa Boudin as District Attorney, followed in 2022 by his recall and removal from office. Boudin had run as a progressive prosecutor, promising fundamental reforms to local crime policy, so the question arises: what, if anything, does his recall just over halfway through his 4-year term of office indicate for the future of progressive prosecution in San Francisco, but equally importantly, throughout the United States? We believe the recall does not signify a broad public retreat from progressive prosecution, which still enjoys wide support in many locales throughout the country, but instead reflects mostly singular characteristics of the San Francisco political system coupled with unique impacts of the COVID pandemic. Still, it represents one variant of the fierce organized opposition that progressive prosecution has engendered everywhere it has been implemented, and therefore, may offer lessons for how to forge ahead with reform measures against determined political resistance.